High Tumor Mitochondrial DNA Content Correlates With an Improved Patient's Outcome in WHO Grade III Meningioma - Hua, Lingyang; Juratli, Tareq A.; Zhu, Hongda; Deng, Jiaojiao; Wang, Daijun; Sun, Shuchen; Xie, Qing; Wakimoto, Hiroaki; Gong, Ye (Frontiers in Oncology, 2020)
Background Studies have shown mitochondrial genome content (mtDNA content) varies in many malignancies. However, its distribution and prognostic values in high-grade meningioma remain largely unknown. In this retrospective study, we sought to assess a putative correlation between the mtDNA content and clinical characteristics. Methods Mitochondrial DNA was extracted from 87 World Health Organization grade III meningioma samples using a qPCR method. The distribution of mtDNA content in WHO grade III meningioma and its correlations with clinical variables were assessed. Furthermore, we Its prognostic values were also determined. Results Mean mtDNA content was 617.7 (range, 0.8 - 3000). There was no mtDNA distribution difference based on the histological subtypes (P = 0.07). Tumors with preoperative radiation were associated with lower mtDNA content (P = 0.041), whereas no correlations with other clinical variables were observed. A high mtDNA content was associated with significantly better PFS (P = 0.044) and OS (P = 0.019). However, in patients who received postoperative radiotherapy, low mtDNA content was associated with better PFS (P = 0.028), while no difference in OS was observed (P = 0.272). Low mtDNA content was also associated with better OS and PFS in subgroups of patients with ER negative status (PFS, P = 0.002; OS, P = 0.002). Conclusions Consistent with other tumors, high mtDNA content was associated with better outcome in WHO grade III meningioma in our cohort. However, for patients who received post-operative radiation therapy, low mtDNA content was associated with better PFS. These findings suggest that mtDNA content may further be explored as a potential biomarker for high-grade meningioma patients and for those who received postoperative radiation therapy.